Kawitwangi Agrotourism Development Strategy and Road Map as a Local Economic Development Effort - Euis Dasipah; Nunung Sondari; Gijanto Purbo Suseno; Tuti Gantini; Aaz Asmudin Tifani (RIRAI Publisher, 2023)
Agrotourism Kawitwangi utilizes natural and agricultural resources for tourist areas, in its development efforts are carried out by strategizing through SWOT analysis followed by Hirarkhi Process Analysis. From the results of the main strategy compiled road map of the stages of agrotourism development, the results of the research showed the main strategy are a) Designing a more effective promotion program by utilizing information technology, especially social media , b) Creating quality tourism products and benefiting the surrounding community through the development of natural tourism in accordance with the government's road map in tourism development in Kawitwangi c) Conducting training activities working with the government to improve service, marketing, management and community utilization d) Cooperate with relevant agencies to be able to facilitate special transportation that facilitates visitors or the public to tourist sites, and maximize road access to tourist attractions e) Involving the Community in Protecting and preserving the environment around tourist attractions. While the development road map with strategic stages d, e, b, ,a dan c. Recomemded are on policy and financial support from the government as well as local community participation for economic growth and empowerment of tourist sites.